INCLUSIVE EDUCATION MODEL WITH MONTESSORI METHOD AND SAVI APPROACH IN EARLY-AGE CHILDREN WITH SPECIAL NEEDS - Dewi Putriani Yogosara Lodewijk; Sitti Hartinah; Yoga Prihatin (SUJANA: Education and Learning Review, 2023)
Inclusive education provides children with special needs and children in general may interact with each other naturally by the demands of daily life in society. In addition, their educational needs can be fulfilled according to their respective potential. This research aims to develop an Inclusive Education Empowerment-based inclusive education model using the Montessori method with the SAVI (Somatic, Auditory, Visual, Intellectual) approach. This research is using R & D method which was conducted in an early childhood education institution with special needs students and teachers in Hamburg, Germany. Primary data were collected directly at school through questionnaires distributed to parents, interviews and observation sheets to observe the activities and development of learners. Secondary data were collected through literature studies related to the focus of this research. Data were analyzed through reduction, data presentation and conclusion drawing. The research findings revealed that the inclusive education model developed could improve the involvement and developmental progress of learners with special needs and strengthen the involvement and support of parents and teachers in supporting students’ development. This inclusive education model is expected to be applied in other educational environments to improve access and equality for children with special needs.